The Problem of Moral Luck by Thomas Nagel and Norvin Richards. - Strzyżyński, Przemysław (Filozofia Chrześcijańska, 2012)
The article discusses the problem of moral luck described by T. Nagel and B. Williams. It also presents the critique of N. Richards. In terms of Nagel moral luck causes a paradox: we judge morally random acts and break the principle of estimating only those acts which are under the con- trol of the perpetrator. Richards criticizes the sole use of the criterion of effects of the act, without intentions. This criticism is extended and includes the objection of too far-reaching generalization of the role of luck made by Nagel.